Peningkatan Higiene Sanitasi Sebagai Upaya Menjaga Kualitas Makanan Dan Kepuasan Pelanggan Di Rumah Makan Dhamar Palembang - T. Prasetyo Hadi Atmoko - AKPARYO (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2017)
ABSTRACT - A very important factors in service are convenience and hygiene guarantee which mean food hygiene and sanitation. The problem formulation in this research is how to improve hygiene and sanitation as an effort to maintain the food quality and customer satisfaction at Dhamar Restaurant Palembang? While the purpose is to acknowledge how to increase hygiene and sanitation as an effort to maintain the food quality and customer satisfaction at Dhamar Restaurant Palembang. The theoretical benefits of this research is to add knowledge in food hygiene and sanitation fields, while the practical benefits are implicated in maintaining quality and customer satisfaction, especially concerning food hygiene and sanitation. The result of this study at Dhamar Restaurant Palembang is to improve hygiene and sanitation to employees, kitchen appliances, and also furnace place so that every products being produced a clean, healthy and has quality. Medical tests for the employees by health authorities in order to the employees are actually in good health therefore the meals spared from the diseases. Showing the expired time in every single foodstuff being served so customers can calculate the time limit of the food. To prevent the health problem for the workers because of cooking activities by having regard to kitchen feasibility standard. Creating a secure atmosphere, comfortable for personnel who involve in food processing. Undertaking cooking place, kitchen equipment always well-preserved. Creating a working situation which are beautifully and healthy. Portions are presented in accordance with the recommendation of health department therefore it complies with a balanced dose of nutritional value. Food quality is matters to note because it acts as a key to business success of food presentation as attractive as possible concerning color, appearance, portion, well-cooked level, taste and flavor. The principle of keeping food quality in Dhamar Restaurant Palembang include in foodstuff selection, foodstuff storage, well-cooked storage, healthy food serving, clean and tidy. The Dhamar customers always feel satisfied, it proved to remain loyal, buy new product offered, recommended food products, are willing to pay more, and provide feedback or suggestions to Dhamar Restaurant Palembang.Keywords: sanitation hygiene, food quality, customer satisfactionAbstrak - Faktor yang sangat penting dalam pelayanan adalah kenyamanan dan jaminan kebersihan yaitu higiene dan sanitasi makanan. Rumusan masalah dalam penelitian ini  bagaimana peningkatan higiene dan sanitasi sebagai upaya menjaga kualitas makanan dan kepuasan pelanggaan di Rumah Makan Dhamar Palembang? Sedangkan tujuannya yaitu untuk mengetahui bagaimana peningkatan higiene dan sanitasi sebagai upaya menjaga kualitas makanan dan kepuasan pelanggan di Rumah Makan Dhamar Palembang. Manfaat teoritis dari penelitian ini adalah menambah ilmu di bidang higiene dan sanitasi makanan, sedangkan manfaat praktisnya dapat diterapkan dalam menjaga kualitas dan kepuasan pelanggan khususnya mengenai higiene dan sanitasi makanan. Hasil dari penelitian ini Rumah Makan Dhamar Palembang meningkatkan higiene dan sanitasi pada karyawan, peralatan dapur serta area dapur agar setiap produk yang dihasilkan bersih, sehat, dan berkualitas. Adanya tes kesehatan bagi karyawan oleh dinas kesehatan supaya karyawan benar-benar dalam keadaan sehat sehingga makanan terhindar dari penyakit. Menampilkan expired time disetiap makanan yang disajikan sehingga pembeli dapat memperhitungkan batas waktu makanan. Mencegah timbulnya masalah gangguan kesehatan pada karyawan karena aktvitas dapur dengan memperhatikan standar kelayakan dapur. Menciptakan suasana aman, nyaman bagi personel yang terlibat dalam pengolahan makanan. Mengupayakan area dapur, peralatan dapur senantiasa terpelihara kesehatannya. Menciptakan suasana kerja yang asri dan sehat. Porsi yang disajikan sesuai dengan anjuran dari dinas kesehatan sehingga sesuai dengan takaran nilai gizi yang seimbang. Kualitas makanan penting untuk diketahui karena berperan sebagai kunci keberhasilan usaha makanan dengan penyajian yang semenarik mungkin mengenai warna, penampilan, porsi, tingkat kematangan, rasa dan aroma. Prinsip menjaga kualitas makanan di Rumah Makan Dhamar Palembang meliputi pemilihan bahan makanan, penyimpanan bahan makanan, penyimpanan makanan masak, penyajian/penjaja Makanan sehat, bersih dan rapi. Pelanggan di Rumah Makan Dhamar selalu merasa puas, hal itu terbukti dengan tetap loyal, membeli produk baru yang ditawarkan, merekomendasikan produk makanan, bersedia membayar lebih, dan memberi masukan atau saran kepada Rumah Makan Dhamar Palembang.Kata Kunci : Higiene sanitasi, kualitas makanan, kepuasan pelanggan.